X-Shooter Survey of Near-Infrared DIBs. Issue Volume 9:Issue S297(2013) (21st February 2014) - Cox, N. L. J.; Cami, J.; Kaper, L.; Foing, B. H.; Ehrenfreund, P.; Ochsendorf, B. B.; van Hooff, S. H. M.; Salama, F.
Abstract: We present the first results of an exploratory VLT/X-Shooter survey of near-infrared diffuse interstellar bands (DIBs) in diffuse to translucent interstellar clouds. These observations confirm the presence of recently discoved NIR DIBs and provide more accurate rest wavelengths and line widths. Example spectra are shown for the reddened, AV ~ 10 mag, line-of-sight towards the distant binary system 4U 1907+09.